Transient medial prefrontal perturbation reduces false memory formation. (March 2017) - Berkers, Ruud M.W.J.; van der Linden, Marieke; de Almeida, Rafael F.; Müller, Nils C.J.; Bovy, Leonore; Dresler, Martin; Morris, Richard G.M.; Fernández, Guillén
Abstract: Knowledge extracted across previous experiences, or schemas, benefit encoding and retention of congruent information. However, they can also reduce specificity and augment memory for semantically related, but false information. A demonstration of the latter is given by the Deese–Roediger–McDermott (DRM) paradigm, where the studying of words that fit a common semantic schema are found to induce false memories for words that are congruent with the given schema, but were not studied. The medial prefrontal cortex (mPFC) has been ascribed the function of leveraging prior knowledge to influence encoding and retrieval, based on imaging and patient studies. Here, we used transcranial magnetic stimulation (TMS) to transiently perturb ongoing mPFC processing immediately before participants performed the DRM-task. We observed the predicted reduction in false recall of critical lures after mPFC perturbation, compared to two control groups, whereas veridical recall and recognition memory performance remained similar across groups. These data provide initial causal evidence for a role of the mPFC in biasing the assimilation of new memories and their consolidation as a function of prior knowledge.